Botanical inventory and phenology in relation to foraging behaviour of the Cape honeybees (Apis Mellifera Capensis) at a site in the Eastern Cape, South Africa,The ecology of honey plants in the Eastern Cape - Merti, Admassu Addi (Rhodes University, Faculty of Science, Botany Department, 2003)
From an apicultural point of view the Cape fynbos is under-utilised and our knowledge of its utilization by the Cape honeybees is incomplete. The key aim of this study was to test the hypothesis that the Cape honeybees utilize the fynbos species as the preferred source of nectar and pollen. Subsidiary aims included distinguishing vegetation communities in the area, identifying pollen and nectar sources, the relationship between brood population and seasonal pollen collection patterns, examining the effect of meteorological factors on pollen collection. The study site was on Rivendell Farm within the Eastern Cape Albany district: an area of high species richness. A checklist of vascular plant species was produced revealing 97 families, 271 genera and 448 species. A classification by two-way indicator species (TWINSPAN) recognized seven vegetation communities: Forest, Bush clumps, Acacia savanna, Grassland, Grassy fynbos, Fynbos and Shrubland. Direct field observations of the foraging of Cape honeybees identified 54 nectar and pollen source plant species. Honeybee pollen loads trapped from four colonies of hives identified 37 pollen source plants of which Metalasia muricata, Eucalyptus grandis, Eucalyptus camaldulensis, Erica chamissonis, Helichrysum odoratissimum, Helichrysum anomalum, Crassula cultrata and Acacia longifolia were the predominant pollen source plants. It was also found that 60% of pollen yield derived from fynbos vegetation. The pollen source plants came from both Cape endemic and from nonendemic species. Thus we reject the hypothesis that Cape honeybees selectively forage fynbos species as a preferred source of pollen and nectar. The examination of the effect of temperature, wind-speed and temperature on pollen collection activity of honeybees revealed that: a temperature range of between 14Â°C to 26Â°C was optimal for pollen collection; wind speeds of up to 4m/s were conducive for pollen collection; relative humidity was found to have no significant influence on pollen collection. Pollen collection and brood rearing patterns are positively correlated with flowering intensities, but we found in our Eastern Cape study site that brood rearing was not limited to the spring flowering season but did extend to the end of summer. In order to determine the available nectar yield of common plant species hourly secretion of nectar volumes was measured for 24 hours to determine the variation of available nectar during different times of the day. In all nectar producing species the nectar volume was high in the early morning and declined as the day progressed. We found that the volume of available nectar was affected by prevailing temperature and humidity around the flowers.
Keywords: Fynbos -- South Africa -- Eastern Cape; Honeybee -- South Africa -- Eastern Cape; Honey plants -- South Africa -- Eastern Cape; Honeybee -- South Africa -- Eastern Cape -- Food; Plant ecology -- South Africa -- Eastern Cape